Catch the spirit teen volunteers tell how they made a difference : stories of inspiration from 20 remarkable recipients of Prudential Spirit of Community Award - Perry, Susan K 1946- (New York Franklin Watts, 2000)
Individual teenagers relate their experiences in various types of volunteer activities
American Corner
Includes bibliographical references (p. 189-190)
11
Keywords: Teenage volunteers in social service -- United States -- Interviews; Voluntarism -- United States; Voluntarism; Volunteers in social service